Multimodal Medical Supervised Image Fusion Method by CNN - Li, Yi; Zhao, Junli; Lv, Zhihan; Pan, Zhenkuan (Frontiers in Neuroscience, 2021)
This paper proposes a multi-mode medical image fusion with CNN and supervised learning, in order to solve the problem of practical medical diagnosis. It can implement different types of multi-modal medical image fusion problems in batch processing mode, and can effectively overcome the problem that traditional fusion problems that it can only be solved by single and single image fusion. To a certain extent, it greatly improves the fusion effect, image detail clarity and time efficiency in new method. And experimental results indicate that the proposed method exhibits state-of-art fusion performance in terms of visual quality and a variety of quantitative evaluation criteria. Its medical diagnostic background is wide.